2019
DOI: 10.1002/biot.201800571
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Commercial Enzymes for Transfructosylation of Tyrosol: Effect of Process Conditions and Reaction Network

Abstract: Enzymatic fructosylation of organic acceptors other than saccharides brings new possibilities to synthesize molecules that do not exist in nature. The introduction of fructosyl moiety may lead to glycosides possessing enhanced physicochemical and bioactive properties which could be useful in the pharmaceutical and cosmetic industry. In this work, the regioselective synthesis of tyrosol β‐d‐fructofuranoside (TF) catalyzed by β‐fructofuranosidase is investigated. In the first step, 32 commercial enzyme preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The period of the fast increase was stopped at this conversion value. The course of sucrose conversion gives an impression of the existence of apparent pseudo-equilibrium at 92%, which is similar to those in our earlier papers [11,16]. However, this longer experiment showed that the sucrose conversion degree grew slowly to 94% during the period of the subsequent transformation of lower FOS oligomers into higher ones.…”
Section: Courses Of Fos Yield and Degree Of Polymerizationsupporting
confidence: 87%
See 2 more Smart Citations
“…The period of the fast increase was stopped at this conversion value. The course of sucrose conversion gives an impression of the existence of apparent pseudo-equilibrium at 92%, which is similar to those in our earlier papers [11,16]. However, this longer experiment showed that the sucrose conversion degree grew slowly to 94% during the period of the subsequent transformation of lower FOS oligomers into higher ones.…”
Section: Courses Of Fos Yield and Degree Of Polymerizationsupporting
confidence: 87%
“…Its specific activity can be directly compared with those of the preparations examined in the paper by Hollá et al, since the same activity determination method was used [16]. Seqenzym ® FT has an about 30 times higher specific activity level than Pectinex Ultra SP-L does and an about 70 times higher level than that of Viscozyme L. The only commercial preparation that could have had the specific activity of the same order of magnitude as Seqenzym ® FT is Rohapect CM [15].…”
Section: Effect Of Enzyme Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most industrial enzyme preparations include not only the main target enzyme but also other contaminating ones. When these preparations are used for food processing, proteases from microbes often lead to contamination (Fia et al, 2014, Hollá et al, 2019. Lactase (β-galactosidase, EC 3.2.1.23) is a glycoside hydrolase enzyme that catalyzes the hydrolysis of lactose to glucose and galactose.…”
Section: Introductionmentioning
confidence: 99%